El FSLN y la «iconización» de Sandino - Catherine Lacaze (Caravelle)
We propose an analyze of the links established by the Sandinista National Liberation Front (FSLN) between the Sandino’s heroization process and the associated «iconization». We focus on three aspects: Sandino as a revolutionary icon, as the archetype of the «true» Nicaraguan and as a mythic figure. The selected period of time relates to the armed struggle against the Somocista dictatorship since the 1960’s, once the Sandinista government came to power in 1979, and after setting up the national reconstruction project (1980-1981).